Are home sleep studies useful in diagnosing obstructive sleep apnea in children with down syndrome?. Issue 10 (9th July 2019) - Ikizoglu, Nilay Bas; Kiyan, Esen; Polat, Beldan; Ay, Pinar; Karadag, Bulent; Ersu, Refika
Abstract: Introduction and Aim: Obstructive sleep apnea syndrome (OSAS) is frequent in children with Down syndrome (DS) and polysomnography (PSG) is recommended for all children with DS. However PSG is not always available and alternative diagnostic methods are needed. The aim of the study was to evaluate the feasibility and validity of home polygraphy (HPG) in children with DS. Methods: A national DS association was contacted and children aged 6 to 18 years who accepted to participate were recruited. Otorhinolaryngologic evaluation, in‐lab PSG and HPG were performed. OSAS was diagnosed by PSG with an apnea‐hypopnea index (AHI) more than or equal to  1. OSAS severity was classified as moderate‐to‐severe if AHI was more than or equal to  5. Receiver operating characteristic curves were calculated for HPG using PSG as the gold standard. Results: Nineteen children (12 girls) completed the study. Median age was 11.3 years. Demographic and clinical characteristics were similar in children with and without OSAS. Eighty‐nine percent of HPG studies were technically acceptable at the initial night and the success rate was 100% when two failed studies were repeated. PSG revealed OSAS in six (32%) children, two had mild and four had moderate‐to‐severe OSAS. All four patients with moderate‐to‐severe OSAS diagnosed with PSG have been diagnosed with the same severity on HPG. HPG had 100% sensitivity and 83% specificity when AHI ≥  3 was set as diagnostic criteria. Conclusion: HPG is a feasible and reliable test of OSAS in children with DS and may be useful in diagnosis and treatment of patients with moderate‐to‐severe OSAS in this patient group.